The Implementation of “Tri Hita Karana” Ideology in Preventing the Spread of Covid-19 in Bali - Nurita, Wayan; Putri, I Gusti Ayu Vina Widiadnya (Celt: A Journal of Culture, English Language Teaching & Literature, 2021)
Abstract: This research examines the form of implementing the local wisdom ideology of Tri Hita Karana in preventing and overcoming the spread of the Covid-19 virus in Bali. The central government, through its policies, has dealt with this epidemic, both at the central and regional levels, including in Bali. In addition to implementing the policies of the central government to prevent and cope with this outbreak, Bali itself attempts to make use of its ideology in dealing with the pandemic. This local ideology is known as Tri Hita Karana. The problem raised in this study is how to implement the ideology of local wisdom in preventing and overcoming COVID-19 in Bali. The purpose of this research is to understand the implementations of local wisdom in Bali that useful in preventing and overcoming COVID-19. The method used is the empirical method, data collection techniques with interviews, questionnaires, and literature. The theory used is structural functional theory, social change theory which supported by concept of local wisdom. The results of this study indicate that the implementation of local wisdom in Bali can effectively and efficiently prevent and cope with COVID-19. An interesting finding of this article is precisely when local wisdom is Tri Hita Karana implemented on a daily basis to deal with Covid-19. The beginning the standard was Prahyangan, Pawongan and Palemahan, however, in this implementation it changed to become Pawongan, Palemahan then Prahyangan.